Características polissonográficas de adultos com doença falciforme - Pedro, Ana Carolina Cabanas [UNIFESP] (2018)
The pathophysiology of sickle cell disease (SCD) is centered on the polymerization capacity of hemoglobin S when deoxygenated, in erythrocytes with reduced deformability and consequent vasoocclusion and hemolysis. The presence of hypoxemia and apnea during sleep is related to clinical manifestations in children with SCD. Our objective was to identify sleep disorders in adults with SCD and to verify a possible relation with the severity of the disease. We studied 100 SCD patients (81 with sickle cell anemia - SS, 19 with hemoglobinopathy SC – SC). We evaluated clinical parameters (pulmonary hypertension - PH and previous manifestation of acute chest syndrome - ACS and stroke), laboratorial data (CBC, reticulocytes, lactate dehydrogenase - LDH, bilirubin and iron profile), polysomnography data (PSG), and oxyhemoglobin saturation (sat oxiHb) during PSG and in wakefulness. The mean age of the patients was 31.7 ± 11.3 years, 58% belonged to the female gender and 62% were on hydroxyurea treatment. Sleep apnea / hypopnea was present in 24% of the patients, most of them mild form, with no difference according to genotype (23% in SS vs. 26% in SC). The total time of sleep and sleep efficiency were lower in subjects with PH (p<0.01 and p=0.04, respectively) and ACS (p=0.06 and p=0.04, respectively). Patients with ACS also had longer N2 time (p<0.01) and shorter N3 time (p<0.01). Patients presented high periodic limb movements indexes (13.8 ± 15.2) and this manifestation was related to hemolysis parameters (indirect bilirubin and reticulocytes), suggesting an association with SCD severity. LDH presented an inverse correlation with sat oxiHb: basal (r=-0.61, 95% CI:-0.73,-0.47, p<0.01); mean (r=-0.61, 95% CI:-0.73,-0.48, p<0.01); wakefulness (r=-0.55, 95% CI:-0.71,-0.35, p <0.01). Comparing subjects with SS and SC, the former had worse sleep efficiency (p=0.04) and lower sat oxiHb indexes during PSG: basal sat oxiHb (SS <SC; p<0.01) and sat oxiHb mean (SS<SC; p<0.01). When we subdivided the group according to sat oxiHb <90 or >90, we observed that those with low sat oxiHb had lower hemoglobin (8.3 ± 1.3 vs. 9.8 ± 1.6, p <0.01) and higher LDH (650 ± 240 vs. 365 ± 155, p<0.01), suggesting a higher degree of hemolysis in these patients. Despite some limitations, this study presents important and previously unobserved aspects in relation to sleep disorders in adults with SCD and reinforces the importance of sleep evaluation in this group of individuals.